(untitled) (Journal on Excellence in College Teaching, 2024)
The purpose of this study was to investigate whether college students’ attitudes toward group work could be influenced by thoughtful group project design. Undergraduate students (N = 123) in a lifespan human development course were assigned to groups and asked to create a smartphone app for a specific life stage. The authors utilized a convergent mixed-method approach to gain a better understanding of which factors (if any) influenced students’ attitudes. Results of paired-samples t tests indicated that students’ attitudes toward group work became more positive over time. Qualitative results revealed several reasons why students enjoyed having assigned group roles. Implications are discussed.